2019
DOI: 10.1111/cas.14017
|View full text |Cite
|
Sign up to set email alerts
|

Three novel genetic variants in NRF2 signaling pathway genes are associated with pancreatic cancer risk

Abstract: Pancreatic cancer (PanC) is one of the most lethal solid malignancies, and metastatic PanC is often present at the time of diagnosis. Although several high‐ and low‐penetrance genes have been implicated in PanC, their roles in carcinogenesis remain only partially elucidated. Because the nuclear factor erythroid2‐related factor2 (NRF2) signaling pathway is involved in human cancers, we hypothesize that genetic variants in NRF2 pathway genes are associated with PanC risk. To test this hypothesis, we assessed ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Literature data regarding SNPs are fragmentary and usually come from case-control studies on different phenotypes, mainly cancers. For example, the variants of rs5757572, rs1800817 and rs2247128 SNPs which improved the results of PROMs were previously associated with increased risk of pancreatic cancer,[ 22 ] gall bladder cancer [ 23 ] and breast cancer. [ 24 ] The fact that these variants are risk factors of the neoplastic process, may suggest that they are rather markers of PDGF-dependent proliferative potential of cells, which would partly explain the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data regarding SNPs are fragmentary and usually come from case-control studies on different phenotypes, mainly cancers. For example, the variants of rs5757572, rs1800817 and rs2247128 SNPs which improved the results of PROMs were previously associated with increased risk of pancreatic cancer,[ 22 ] gall bladder cancer [ 23 ] and breast cancer. [ 24 ] The fact that these variants are risk factors of the neoplastic process, may suggest that they are rather markers of PDGF-dependent proliferative potential of cells, which would partly explain the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have identified body mass index as a causative factor for PDAC development using a Mendelian randomization approach 8‐10 . The genetic susceptibility to PDAC is the result of the involvement of rare high penetrance mutations and high frequency low penetrance variants discovered through genome wide association studies (GWAS) or large multicentric candidate gene approaches 11‐22 …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The genetic susceptibility to PDAC is the result of the involvement of rare high penetrance mutations and high frequency low penetrance variants discovered through genome wide association studies (GWAS) or large multicentric candidate gene approaches. [11][12][13][14][15][16][17][18][19][20][21][22] The recent advances in the knowledge on the regulatory regions of the human genome have highlighted that several GWAS hits associated with a variety of human traits, including PDAC risk, are located in DNA sequences containing noncoding RNA (ncRNA). 23 The vast majority of ncRNAs consists of long noncoding RNA (lncRNA), and recent evidences suggest that around 68% of the human transcriptome consists of lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rare high-penetrance mutations and high-frequency lowpenetrance variants, discovered through genome-wide association studies (GWASs), contribute, alone or in combination, to the genetic susceptibility of PDAC (7)(8)(9)(10)(11)(12)(13)(14)(15). Additional susceptibility variants have been identified through large multicentric gene candidate approaches and through secondary analysis of published GWAS data (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The number of identified loci is, however, very small if compared with breast, prostate or colorectal cancers and the fraction of the heritability they explain is limited.…”
Section: Introductionmentioning
confidence: 99%